The Effects of Leguminous Seed Extracts on Blood Coagulation - Speer, R. J; Porter, J. L (Thrombosis and Haemostasis, 1962)
The saline extracts of one hundred leguminous seed were screened for their effect on blood coagulation by the following tests: thrombin clot time, recalcification time, Quick prothrombin time, clot lysis and clot retraction. Nineteen of these extracts, when reacted with normal plasma, gave a prolonged clot time in at least one of two tests: recalcification time and Quick prothrombin time. The eight which gave a prolonged Quick prothrombin time were tested for inhibition in the following assay systems: Factor V, factor VII-complex, and prothrombin. All nineteen, including the seventeen which prolonged the re-calcification time and the two which did not, were tested for their inhibitory action in the following assay systems: Factor VIII, factor IX, and plasma thromboplastin antecedent.The inhibition of prothrombin, factor V, and factor VII-complex was mild and not specific for any of these factors. Factor V activity was depressed more than the other two. By contrast, the inhibition of factor VIII, factor IX, and plasma thromboplastin antecedent was very strong and demonstrated a relatively high degree of specificity.